Modelling Exchange Rates and PMS Prices Impact on Inflation in Nigeria (1985-2020): A Regression Analysis - Gwani, Alhaji Abdullahi; Farouk, Abbas Umar; Mukhtar; Sek, Siok Kun (Universitas Islam Indonesia, 2024)
On the rise in Premium Motor Spirit (PMS) prices and cash rates, a conventional least squares analysis was used to determine the relationship between the respondent variable, inflation, and the explanatory variables, PMS price and exchange rate. According to the results, as evidenced by the conventional least squares regression, the PMS price and money rate were significant drivers of inflation, accounting for about 88% of the fluctuation in inflation. Additionally, the Breusch-agnostic test revealed that the residuals of the direct regression model were not heteroscedastic, and the ACF and PACF tests revealed that the error terms did not have autocorrelation. The Jarque-Bera ordinariness test was used to express the perceived background noise as normal. As demonstrated by the findings, the increase in the price of PMS and the decline in the value of the Naira influenced Nigerian inflation. Finally, based on the research econometric outcomes and interpretations, the study discussed the policy implications of these findings and offered recommendations. For future work, research should be conducted on energy transition and efficiency.